In vitro IL-6/IL-6R Trans-Signaling in Fibroblasts Releases Cytokines That May Be Linked to the Pathogenesis of IgG4-Related Disease - Zongfei, Ji; Rongyi, Chen; Xiaomeng, Cui; Lili, Ma; Lingying, Ma; Xiufang, Kong; Xiaomin, Dai; Zhuojun, Zhang; Huiyong, Chen; Ying, Sun; Lindi, Jiang (Frontiers in Immunology, 2020)
Background: The mechanisms of remarkable storiform fibrosis and high levels of IgG4 with a pathogenic germinal center (GC) formation in the inflammatory tissue of IgG4-RD remains unknown and may be responsible for the unsatisfactory therapeutic effect using conventional therapy. Objectives: To investigate the mechanism of interleukin 6 (IL-6) inducing fibroblasts to produce cytokines for pathogenic GC formation in the development of IgG4-related disease (IgG4-RD). Methods: The clinical data and laboratory examinations of 56 patients with IgG4-RD were collected. IL-6 and IL-6R expression in the serum and tissues of patients with IgG4-RD and healthy controls was detected by ELISA, immunohistochemistry, and immunofluorescence. Human aorta adventitial fibroblasts (AAFs) were cultured and stimulated with IL-6/IL-6 receptor (IL-6R). The effect of IL-6/IL-6R on AAFs was determined by Luminex assays. Results: The serum IL-6 and IL-6R levels were elevated in active IgG4-RD patients and IL-6 was positively correlated with the disease activity (e.g., erythrocyte sedimentation rate [ESR], C-reactive protein [CRP], and IgG4-RD responder index). IL-6 and IL-6R expression in the tissue lesions of IgG4-related retroperitoneal fibrosis and IgG4-related sialadenitis patients were also significantly higher than that in the normal tissues. In addition, there is a relative abundance of myofibroblasts as well as IgG4+ plasma cells in the tissue of IgG4-related retroperitoneal fibrosis. α-SMA and B cell differentiation cytokines (i.e., B cell activating factor), α-SMA and T follicular helper (Tfh) cell differentiation cytokines (e.g., IL-7, IL-12, and IL-23) were co-expressed in the local lesions. In vitro, IL-6/IL-6R significantly promoted the production of B cell activating factor, IL-7, IL-12, and IL-23 in AAFs in a dose-dependent manner. This effect was partially blocked by JAK1, JAK2, STAT3, and Akt inhibitors, respectively. Conclusions: In vitro IL-6/IL-6R trans-signaling in fibroblasts releases Tfh and B cell differentiation factors partially via the JAK2/STAT3, JAK1/STAT3 and JAK2/Akt pathways, which may be linked to the pathogenesis of IgG4-RD. This indicated that IL-6 and fibroblasts may be responsible for GC formation and fibrosis in the development of IgG4-RD. Blocking IL-6 with JAK1/2 inhibitors or inhibiting fibroblast proliferation might be beneficial for IgG4-RD treatment.